Private equity investment committee paper on Aveleda, S.A. –Aveleda: performing an LBO takeover in the main Portuguese vinho verde producer - Carvalho, Tomás Quartin Bastos De Almeida de (2020)
Aveleda represents one of the most recent success cases of Portuguese wine producers. Leveraging on its heritage and reshaping Vinho Verde’s prestige around the world, Aveleda has taken advantage of the recent market trends. The Private Equity market appetite for companies with stable cash flows, further development opportunities and efficiency gains determines this investment decision. Aveleda’s business plan is grounded on a Buy-and-Build strategy (with the acquisition of Quinta do Vallado), internationalization intensification and a complementing real estate strategy. The forecasted returns (3.4x Money Multiple and 27.5% Internal Rate of Return) highlight the unique opportunity that is investing in Aveleda. Underpinned by the proper management incentives, the construction of both conservative and optimistic scenarios and the optimization of Aveleda’s capital structure, this investment presents an un parallel financial and strategic opportunity.